Sistem Pendukung Keputusan Dalam Menentukan Kepala Bengkel Terbaik Menggunakan Metode AHP dan WSM - Ramadina Pertiwi; Natalia Silalahi; Fince Tinus Waruwu (Bulletin of Computer Science Research, 2021)
The selection of workshop heads requires an interactive computer-based system that helps decision makers to use data and various models in solving structured problems. One of the selections for the Head of the Workshop is the Decision Support System. Decision Support System is an interactive information system that provides information, modeling and manipulating data. There are many methods used in making decisions in every important data in the form of the number of units per year, the number of services per year, the number of sales of spare parts per year, years of service and discipline, one of which is the AHP and WSM method. AHP is a functional hierarchy with human perceptual input, WSM is a general model, it has been used for different applications such as robotics, processors, and others. The AHP method is used to find the criteria for selecting the best workshop head and the WSM method is used to find the final result of the selection of the workshop head. The results show that the best workshop heads will get rewards in the form of traveling abroad with their families. Thus, the results of the designed system will assist the Company in conducting the selection process for the best workshop heads. however, the calculation only produces the largest value which will be selected as the best alternative